2019
DOI: 10.5014/ajot.2019.030080
|View full text |Cite
|
Sign up to set email alerts
|

Italian Version of the Jebsen–Taylor Hand Function Test for the Assessment of Hand Disorders: A Cross-Sectional Study

Abstract: Importance: Having a test to evaluate hand function is fundamental to occupational therapy practice. Objective: To assess the psychometric properties of the Italian version of the Jebsen–Taylor Hand Function Test (JTHFT). Design: Cross-sectional study. Setting: Three health care institutions in Rome, Italy. Participants: 136 people with injuries, burns, or neurological diseases of the hand. Intervention: No intervention was provided. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…the research group has carried out of many outcome measures in italy. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] the objective of the study was to analyze outcome differences between heterogeneous rehabilitation programs, paying attention on elements such as program supervision, intensity and start timing. MiNerVa OrtOpedica e trauMatOlOgica 11 0.23 points improvement of the standard rehabilitation group in the first one and of 0.43 points compared to the 0.27 points of the control group in the second one.…”
Section: Discussionmentioning
confidence: 99%
“…the research group has carried out of many outcome measures in italy. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] the objective of the study was to analyze outcome differences between heterogeneous rehabilitation programs, paying attention on elements such as program supervision, intensity and start timing. MiNerVa OrtOpedica e trauMatOlOgica 11 0.23 points improvement of the standard rehabilitation group in the first one and of 0.43 points compared to the 0.27 points of the control group in the second one.…”
Section: Discussionmentioning
confidence: 99%
“…In the original study, the Grasp-Release Test (GRT) [10] and the Jebsen-Tylor Hand Function Test [6] were used as the gold standard. Considering that the GRT has not been validated for the Italian population, and that the Jebsen-Taylor Hand Function Test was been validated after the start of the study [19,20] for the present study, the Italian version of the SCIM III [30] was used to determine validity. To measure the responsiveness of the IT-VLT between T0 and T1, a pairedsamples t test was used.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to extend the sample size allowing a better understanding of the relationship between the VLT score and different levels of C-SCI. Furthermore, further work is needed to examine interrater reliability and concurrent validity with the Jebsen-Taylor Hand Function Test now available in its Italian valid and reliable version [19,20]. This work also lays the basis for developing and investigating the psychometric properties of the short version of the IT-VLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jebsen-Taylor Hand Function Test (JTHFT;Jebsen et al, 1969) is one of the most widely used assessment tools for investigating hand dexterity, and it has been a recommended tool for the CP population (Castelli et al, 2016;Wagner & Davids, 2012). The Italian version of the JTHFT-IT has been validated on samples of people without health problems (Culicchia et al, 2016), in a nonspecific disease sample (Nobilia et al, 2019) and among patients with rheumatoid arthritis (Savona et al, 2019). All of these studies demonstrated good psychometric (reliability and validity) properties.…”
Section: Introductionmentioning
confidence: 99%